Pectinifera rootstock for quality fruits and high density planting in mandarins under Thar desert - Gora, Jagan Singh; Kumar, Ramesh; Jat, Akheram (Indian Horticulture, 2025)
Rootstock is a key factor in citriculture for better climatic adaptability, compatibility with canopy architecture, higher production, quality harvest, and a healthy and longer orchard life. After evaluation of different scion-rootstock combinations at ICAR-Central Institute of Arid Horticulture (CIAH), Bikaner, Pectinifera (Citrus pectinifera) has been found to be a superior rootstock in Kinnow, Daisy and Fremont cultivars of mandarin for horticultural interests like high density planting, compact canopy, early harvesting and high yield with quality fruits. It was also least affected by biotic and abiotic stresses of the arid region such as fruit cracking, sun-burning, citrus canker, and sucking moth. This promising rootstock will be beneficial for mandarin growers in the recently expanded citriculture industry under Indira Gandhi Nahar Pariyojana (IGNP) command area, which has good quality water supply in the Thar desert.